Tax avoidance in South Africa: an investigation of how the introduction of S 80A-80L closed the loopholes in the now-repealed S 103(1) - Dube, Sfiso (My University, 2020)
Tax avoidance in South Africa has evolved over the years, which results in tax planning and structuring being skewed. On the one hand, taxpayers try and arrange their affairs to pay the least amount of tax, while on the other hand the revenue authorities try and close all the loopholes. This research report will investigate how the introduction of General Anti-Avoidance Rules in s 80A- 80L closed the loopholes in the now-repealed s 103(1) General Anti-Avoidance Rules. The research will first make a distinction between tax avoidance, tax evasion and tax planning. It will further examine the requirements under the now repealed General Anti-Avoidance Rules (GAAR) in s 103(1) and the ones in the new s 80A-80L of the Act to identify these loopholes
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Commerce (Specialising in Taxation), 2020